Prompting Learnersa Active Participation in an EFL Class (Global Journal of Human-Social Science, 2015)
This paper seeks to explore the dynamic relationships between cognitive, affective, and psychomotor components of EFL learners in the classroom, to work out solutions to the problems encountered by those reticent learners. This paper also attempts to describe the underlying dynamic of the three components by borrowing the ideas from physics and mathematics such as Newton's three laws along with important concepts from vector calculus ( ∇ del, ∇ • f, ∇ × f ) in order to determine the relative rates (gradient), level of diversity, and level of curl among the three components. The description on the basis of three-dimensional coordinates helps clarify the complexity involved in the types of reticent EFL learners, each of which features unique combinations of the three components, and specific instructional approaches of different orientations (cognitive, affective, and behavioral, or combined) are suggested such as Jigsaw, Vygotsky's social-constructive, content-based, task-based, competence-based, and operant conditioning, and the like, to deal with EFL reticent learners of different types. The model presented in this paper ushers more empirical studies on relevant issues in EFL instruction.
Keywords: types of reticent EFL learners; each of which features unique combinations of the three components; and specific instructional approaches